Renal clearance estimated by rubidium‐82 positron emission tomography/computed tomography and technetium‐99m‐mercaptoacetyltriglycine clearance infusion technique - Langaa, Stine Sundgaard; Duus, Camilla Lundgreen; Vrist, Marie Houmaa; Mose, Frank Holden; Fynbo, Claire Anne; Theil, Jørn; Ejlersen, June Anita; Bech, Jesper Nørgaard (Clinical physiology and functional imaging, 2025)
Background Although numerous techniques exist for renal blood flow (RBF) estimation, none of the methods have been implemented in routine clinical practice due to their inadequacies and burdensomeness. Previously, we evaluated rubidium‐82 (82Rb) positron emission tomography/computed tomography (PET/CT) for renal perfusion determination and found strong indications of method precision and reliability. The aim of this study was to compare renal 82Rb clearance with renal technetium‐99m‐mercaptoacetyltriglycine ([99mTc]Tc‐MAG3) clearance as a first attempt to validate 82Rb PET/CT for renal perfusion estimation using a reference method. Methods Ten subjects with essential hypertension underwent two treatment periods, receiving spironolactone and placebo in random order. At the end of each period, each subject completed a 82Rb PET/CT scan and a [99mTc]Tc‐MAG3 clearance study. Results 82Rb clearance correlated positively with [99mTc]Tc‐MAG3 clearance in both treatment periods. The [99mTc]Tc‐MAG3‐to‐82Rb clearance ratio was 0.83 and 0.86 in the placebo and spironolactone treatment periods, respectively. Conclusion The correlation between 82Rb clearance and [99mTc]Tc‐MAG3 clearance may indicate that PET/CT determined 82Rb clearance can act as an estimator of renal perfusion. The [99mTc]Tc‐MAG3‐to‐82Rb clearance ratios suggest that the extraction fraction of 82Rb is higher than that of [99mTc]Tc‐MAG3, further suggesting 82Rb clearance as an estimator of flow. However, further studies are warranted to validate use of 82Rb PET/CT for flow estimation.